Imaging and bone marrow assessments improve minimal residual disease prediction in multiple myeloma. Issue 8 (9th June 2019) - Alonso, Rafael; Cedena, María Teresa; Gómez‐Grande, Adolfo; Ríos, Rafael; Moraleda, José María; Cabañas, Valentín; Moreno, María José; López‐Jiménez, Javier; Martín, Fernando; Sanz, Alejandro; Valeri, Antonio; Jiménez, Ana; et al.
Abstract: The value of minimal residual disease (MRD) status by bone marrow and imaging analysis as independent prognostic factors has been well established in multiple myeloma (MM). Nevertheless data about their potential complementarity for a more accurate assessment are limited. With this aim, we retrospectively analyzed the prediction of outcome with the combination of PET‐CT and MRD, assessed by multiparameter flow cytometry (MFC) in 103 patients with newly diagnosed MM. We confirmed the benefit in terms of progression‐free survival (PFS), linked to the achievement of negativity by MFC (hazard ratio [HR] 0.53; 95% confidence interval [CI]: 0.28‐0.98), and PET‐CT (HR 0.18; 95% CI: 0.09‐0.36) individually. By combining both techniques, patients who became MRD‐/PET‐, with a median of PFS 92 months, had significant prolonged median PFS ( P < .001). This is compared with MRD+/PET‐ and PET+ patients (median PFS of 45 and 28 months, respectively). We observed a significant difference ( P = .003) in overall survival (OS) outcomes between MRD‐/PET‐ and MRD+/PET‐ patients (4‐year OS 94.2% and 100%, respectively), vs PET+ patients (4‐year OS 73.8%). All survival results were confirmed in a conditional landmark analysis. These findings support the potential complementarity between PET‐CT and MFC, and highlight their better predictive capability when improving sensitivity.